TINJAUAN KURIKULUM MATA KULIAH BAHASA INGGRIS PADA PROGRAM STUDI PENERANGAN AERONAUTIKA SEKOLAH TINGGI PENERBANGAN INDONESIA - Nurtiara Putri, Shanty; Rosmayanti, Lina (Langit Biru: Jurnal Ilmiah Aviasi, 2013)
This research war conducted in to analyze relevancy between curriculum of English language with AIS reference and degree of achievement of Aeronautical Informasi (AIS) trainee in English language. Curriculum of English language in AIS Training Division was decribed with reference of ICAO Document 7192 AIS Training Manual and Document 9835 Manual Manual on the Implementation of ICAO Language Proficiency Part II ICAO Language Proficiency.The method used was descriptive method. Data collecting was conducted using projection test of trainee's achievement which are consist of AIS bacth 5 and AIS bacth 6. The result was 27,65%.Based on the of the research, it can be concluded that AIS trainee's achievement in English language can be improved through the improvement of curriculum and syllabus with reference to ICAO requirement, therefore trainees can achieve in ICAO Language Proficiency (ILP) level 3 (Operational).